Protoplast formation and regeneration in lactobacillus delbrueckii - Singhvi, Mamta; Joshi, Dipti; Gaikaiwari, Shalaka A.; Gokhale, Digambar V. (Indian Journal of Microbiology, 2010)
Method for production and regeneration of Lactobacillus delbrueckii protoplasts are described. The protoplasts were obtained by treatment with a mixture of lysozyme and mutanolysin in protoplast buffer at pH 6.5 with different osmotic stabilizers. The protoplasts were regenerated on deMan, Rogosa and Sharpe (MRS) with various osmotic stabilizers. Maximum protoplast formation was obtained in protoplast buffer with sucrose as an osmotic stabilizer using a combination of lysozyme (1 mg/ml) and mutanolysin (10 mu g/ml). Maximum protoplast regeneration was obtained on MRS medium with sucrose (0.5 M) as an osmotic stabilizer. The regeneration medium was also applicable to other species of lactobacilli as well. This is, to our knowledge, the first report on protoplast formation and efficient regeneration in case of L. delbrueckii.
Keywords: Lactobacillus delbrueckii; Protoplast formation; Protoplast regeneration

Development of biocatalysts for production of commodity chemicals from lignocellulosic biomass - Adsul, Mukund G.; Singhvi, M. S.; Gaikaiwari, Shalaka A.; Gokhale, D. V. (Bioresource Technology, 2011)
Lignocellulosic biomass is recognized as potential sustainable source for production of power, biofuels and variety of commodity chemicals which would potentially add economic value to biomass. Recalcitrance nature of biomass is largely responsible for the high cost of its conversion. Therefore, it is necessary to introduce some cost effective pretreatment processes to make the biomass polysaccharides easily amenable to enzymatic attack to release mixed fermentable sugars. Advancement in systemic biology can provide new tools for the development of such biocatalysts for sustainable production of commodity chemicals from biomass. Integration of functional genomics and system biology approaches may generate efficient microbial systems with new metabolic routes for production of commodity chemicals. This paper provides an overview of the challenges that are faced by the processes converting lignocellulosic biomass to commodity chemicals. The critical factors involved in engineering new microbial biocatalysts are also discussed with more emphasis on commodity chemicals. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biomass utilization; Commodity chemicals; Ethanol; Lactic acid; Microbial cellulases